2018
DOI: 10.1590/1678-4685-jbn-3825
|View full text |Cite
|
Sign up to set email alerts
|

Posterior reversible leukoencephalopathy syndrome (PRES) after kidney transplantation: a case report

Abstract: PRES is an unusual complication after organ transplantation and should be considered in the appropriate clinical setting. Physicians must be aware of this condition in order to provide early detection and appropriate treatment since delay in removing the cause may lead to permanent sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The occurrence of PRES in patients after transplantation secondary to tacrolimus is well-documented in the literature. This phenomenon has been observed in patients who have received liver ( 1 4 ), heart ( 5 , 6 ), kidney ( 7 – 9 ), and multivisceral transplants ( 10 ). In a retrospective chart review of 4,222 patients who underwent solid organ transplants, PRES developed in 21 (0.49%) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 86%
“…The occurrence of PRES in patients after transplantation secondary to tacrolimus is well-documented in the literature. This phenomenon has been observed in patients who have received liver ( 1 4 ), heart ( 5 , 6 ), kidney ( 7 – 9 ), and multivisceral transplants ( 10 ). In a retrospective chart review of 4,222 patients who underwent solid organ transplants, PRES developed in 21 (0.49%) patients ( 11 ).…”
Section: Discussionmentioning
confidence: 86%
“…Each reported case of postoperative PRES was analyzed from the perspective of the pathology of interest, going on to hypothesize, for example, the role of primary damage to the BBB in cases of operated posterior cranial fossa lesions [15,18,46], or immunosuppressive therapy [17,20,21,39,40] in patients undergoing organ transplantation [35,52]. Instead, we believe that in individuals predisposed to have primary endothelial damage, a stressful incident such as surgery of whatever type may result in postoperative PRES in rare cases.…”
Section: Discussionmentioning
confidence: 99%
“…Five weeks after transplantation, she was admitted to the emergency due to RPES, manifested by sudden onset of confusion, disorientation, visual disturbances, and major headache. [ 17 ] Another case-control study, including 51 patients receiving tacrolimus, cyclosporine or prednisolone owing to nephrotic syndrome, of these 21 with RPES and 30 without, found that hypertension, proteinuria, hypercholesterolemia, and lower serum albumin levels were more common in RPES patients. [ 18 ] Our patient also had these risk factors, but not clear whether is caused by RPES.…”
Section: Discussionmentioning
confidence: 99%